2020
DOI: 10.21203/rs.3.rs-15551/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of cardiorespiratory fitness and sleep duration in early CVD prevention. BMI, resting heart rate and questions about sleep patterns are suggested in risk assessment of young adults, 18-25 years.The cross-sectional Lifestyle, biomarkers and atherosclerosis (LBA) study.

Abstract: Background: Cardiorespiratory fitness (CRF) and sleep habits are lifestyle factors with potential to prevent cardiovascular disease (CVD). CVD is the leading cause of death worldwide, it is therefore important to establish a healthy lifestyle at young age. In the Lifestyle, biomarkers and atherosclerosis (LBA) study we have examined 834 healthy non-smoking adults, 18-25 years. The general purpose of the LBA study was to study the effect of lifestyle on traditional biomarkers known to influence CVD risk. The ai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A significant inverse association between sleep duration and HOMA‐IR was noted in the entire sample, suggesting that those with shorter sleep durations have less advantageous HOMA‐IR/greater insulin resistance. These results corroborate prior findings in emerging adults (Fernström et al, 2020), and provide further evidence of an association between short sleep duration and HOMA‐IR as a risk factor for cardiometabolic disease in this population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A significant inverse association between sleep duration and HOMA‐IR was noted in the entire sample, suggesting that those with shorter sleep durations have less advantageous HOMA‐IR/greater insulin resistance. These results corroborate prior findings in emerging adults (Fernström et al, 2020), and provide further evidence of an association between short sleep duration and HOMA‐IR as a risk factor for cardiometabolic disease in this population.…”
Section: Discussionsupporting
confidence: 91%
“…wake‐time – ½ sleep duration), as well as greater day‐to‐day sleep duration and sleep timing variability are associated with greater adiposity and adverse cardiometabolic outcomes (Chaput et al, 2020; Morales‐Ghinaglia & Fernandez‐Mendoza, 2023). Consistent evidence suggests that emerging adults and college students with shorter sleep duration and/or poorer sleep quality have greater adiposity (Bailey et al, 2014; Fernström et al, 2020; Kahlhöfer et al, 2016; Krističević et al, 2018; Meyer et al, 2012; Peltzer & Pengpid, 2017; Quick et al, 2014; Sa et al, 2020; Vargas et al, 2014; Yang et al, 2020), but much of this evidence is limited to self‐reported sleep variables and/or using body mass index (BMI) as a single indicator of adiposity/obesity.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation